Improved Semantically Secured Variant of RSA Public Key Cryptosystem - Sushma Pradhan; Birendra Kumar Sharma (Institute of Advanced Engineering and Science, 2015)
Boneh and Shacham gave a nice survey on four variants (Batch RSA, Multi-Prime RSA, Multi-Power RSA, and Rebalanced RSA). Batch RSA and Multi-Prime RSA were then combined to increase the decryption/signature generation performance. Here in this paper we further tried to increase the encryption/ signature verification performance. The proposed scheme is semantically secure also.